EFFECT OF TENDON GLIDING EXERCISES S FOR BILATERAL CARPAL TUNNEL SYNDROME AFTER SAUVE-KAPANDJI PROCEDURE - Annisa Dwi Rahayu ,; Isnaini Herawati ,; Purbasasana, Purbasasana (Jurnal Cakrawala Ilmiah, 2025)
Introduction: Bilateral Carpal Tunnel Syndrome (CTS) post Sauve-Kapandji is a complication following the Sauve-Kapandji procedure, characterized by wrist pain, stiffness, and swelling. These symptoms impair hand function and daily activities, necessitating effective rehabilitation strategies. Early intervention is essential to prevent long-term disability. Purpose: To evaluate the effectiveness of Tendon Gliding Exercises in managing bilateral CTS post Sauve-Kapandji and improving functional outcomes. Methods: A case repost was conducted at Dr. Sardjito Hospital on a 51-year-old female patient diagnosed with bilateral CTS post Sauve-Kapandji. Interventions included Tendon Gliding Exercises performed twice weekly for four weeks, supported by medications. Evaluations used tools such as Numeric Pain Rating Scale (NRS), Manual Muscle Testing (MMT), goniometry, and Wrist Hand Disability Index (WHDI). Results: After eight sessions, significant improvements were observed: pain intensity decreased from 5/10 to 3/10, muscle strength increased from 3/5 to 4/5, ROM improved (flexion: 30° to 50°; extension: 30° to 40°), and WHDI scores dropped from 21 to 18. However, optimal functional recovery requires extended therapy and adherence to home-based exercises. Conclusion: Tendon Gliding Exercises effectively reduce symptoms and improve physical function in bilateral CTS post Sauve-Kapandji. Extended therapy duration and consistency are crucial for maximizing functional recovery.